Membangun kesehatan mental anak usia dini dengan pengasuhan positif - Dewi Retno Suminar; H Hamidah (Utan Kayu Publishing, 2021)
Early childhood who are in PAUD often get developmental stimulation. Apart from providing stimulation, Bunda and Yanda are the closest people to PAUD apart from their parents. Parenting principles are also applied in PAUD. Good parenting at an early age will make children grow up well in the future. A person's mental health problems are often related to early parenting. On this basis, counseling on positive parenting for Bunda and Yanda in early childhood education was carried out. The socialization activities were carried out in Dengok Village, Padangan District, Bojonegoro Regency. Activities carried out to provide solutions to existing parenting problems. Counseling is carried out in two days at intervals of one week to provide opportunities for Bunda and Yanda in PAUD to look for parenting problems in the field so far. The results obtained are quite encouraging because of the increased understanding of Mothers and Yanda in PAUD about positive parenting methods which in turn will make children happier and improve mental health.